PENJADWALAN REPARASI TUG BOAT MENGGUNAKAN METODE CPM DAN PDM - Mochammad Ikhsan Nudin; Kharis Abdullah (Fakultas Sains dan Teknologi Universitas Karimun, 2023)
At this time the shipyard industry is growing more rapidly which makes the owners of the company compete to be better and faster, especially in the field of repair, especially the type of tug boat. The existence of tug boats is quite a lot in Indonesia because it can operate in various fields, so the frequency of docking in shipyards is often found. Project management in the field of repair scheduling is prioritized in order to accelerate the duration of ship repairs. In the scheduling process, the CPM (Critical Path Method) method and the PDM (Precedence Diagram Method) method which are project management methods are widely used to determine the critical path so that acceleration can be carried out in a project work. With this method, the total duration of the tug boat repair work is obtained for 18 days.